Automated Speed Control - Guna, Raja (UTeM, 2009)
This project is aimed to design and build a control system that keeps the speed of DC motor at a certain speed. The PLC (Programmable Logic Controller) is used as a controller to control the speed of DC motor. Optoelectronic sensor will be used to measure the speed of DC motor. In this system, the photo detector sensor was used for measure the rotation speed of DC motor. This system is also can measure the speed of rotation even there is any disturbance occurred in systems. The disturbances could be such as oil or water. When there is any disturbance occurred in system, the PLC will be triggered and control the rotation of motor to the setting speed. There are three types of disturbance that can be adapted to the system, which are zero disturbances, low disturbance and high disturbance. The zero disturbances will not give any effect to the system. However, the low disturbances will slower the speed of rotation a little and the high disturbance will slower the speed quite big. The main objective ofthis project is to design a system with PLC to measure the speed of rotation of DC motor even there is any disturbance cored in systems. The speed of rotation can be detected by using the optoelectronic sensor. This LED will produce a beam of light to rotated disk. The interrupted beam light will be captured by the photo detector and the speed will be measured. The PLC acts as a main part in this project as it triggers and controls the whole circuit. The PLC controller is controls the speed of rotation. There are three types of speed conditions will be measured. There are high speed, medium speed and low speed. The measured speed will be display in a seven segment display or LCD. However, the reading that displays in seven segments are depends to the capability of the light sensor.